Zagrożenia i szanse rozwojowe rynku cukierniczego w Polsce - Szwacka-Mokrzycka, Joanna; Kociszewski, Michał (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2013)
The aim of the article is to present the directions of confectionery market development in Poland. The special attention has been paid to the opportunities and threats of this market. The considerations are started from presentation of the confectionery market structure, its main players. There has been discussed the direction of consolidation activity. The crucial attention has been paid to directions and possibilities of promotion this market by export.